E-Book publishing in Spain. Issue 4 (29th July 2014) - Antonio Cordón-García, José; Linder, Daniel; Gómez-Díaz, Raquel; Alonso-Arévalo, Julio
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The aims of the present paper is electronic publishing has transformed the business model of publishing houses in Spain in such a way that two models currently coexist. The specificities of each of these models were studied and the consequences of each model for the future of electronic publishing in Spain were analysed. Design/methodology/approach – The first stage of this study consisted in locating studies that would allow the authors to obtain useful indicators and statistic data regarding publication in Spain. The second stage of this study consisted of extracting from the sources cited above all data relevant to the study. To wit, these were the number of electronic books published, the major publishing houses offering electronic publications, the major platforms currently selling electronic books, presently available electronic reading devices, the rates of reading on all devices, reading rates itemized by age and educational background and general tendencies in digital publishing and e-reading. Findings – There are traditional publishers of mostly paper-based volumes, whose business models are based on having large catalogues of titles and large print-runs, though print-runs are increasingly smaller and bookseller returns increasingly larger. Intermediary agents operating under this model, for instance booksellers, are subject to ever-greater economic pressures, especially in the current crisis Originality/value – In the study that follows, the authors attempt to analyse the characteristics behind these changes and learn to what extent these changes will affect the future models of publication and reading in Spain.